2019
DOI: 10.1002/mop.31830
|View full text |Cite
|
Sign up to set email alerts
|

Novel circularly polarized dielectric resonator antenna for microwave image sensing application

Abstract: In this article, a novel, simple, and compact structure of dielectric resonator antenna is proposed, which provides wide bandwidth across proposed mm wave band for microwave image sensing with considerable gain using a lossy FR‐4 epoxy substrate and thick FR4 as DRA. A DR can be excited using four‐line feed using a circular loop type feed network. These line feeds maintain phase difference of 90° to produce CP. This antenna provides approximate constant gain of 8.6 dB on 25‐26 GHz band and 3 dB axial ratio ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Moreover, this design results in a narrower 3 dB ARBW of 3.9%. Circular polarization is achieved by employing a feeding technique that consists of a circular microstrip line with four open stubs in [12]. The design has a large feed footprint, comparable −10 dB IBW, and a narrow 3 dB ARBW of 2.92%, but a higher CP gain of 8.6 dBic than the proposed design.…”
Section: Measured Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this design results in a narrower 3 dB ARBW of 3.9%. Circular polarization is achieved by employing a feeding technique that consists of a circular microstrip line with four open stubs in [12]. The design has a large feed footprint, comparable −10 dB IBW, and a narrow 3 dB ARBW of 2.92%, but a higher CP gain of 8.6 dBic than the proposed design.…”
Section: Measured Resultsmentioning
confidence: 99%
“…In [15], a complex cylindrical stair shape of the DR is adapted that obtains a wider −10 dB IBW and 3 dB ARBW and lower CP gain as compared to the proposed design. Moreover, unlike the geometries in [7], [10]- [12], and [15], the proposed structure is simple, compact, and uses Nylon screws to hold the DR firmly to the ground, thereby making it resistant to flickering.…”
Section: Measured Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that most of the existing DRA structures used for RBMI are multistatic (use of more than one antenna for tumor detection) and are bigger in size 22,23 . Many of the investigators did not authenticate their method experimentally using mimic of female breast 24,25 . The proposed monostatic method implicates the usage of a UWB antenna for S 11 parameter as associated to other wideband DRAs and microstrip patch antennas for RBMI 16,23‐25 .…”
Section: Microwave Imaging Of the Breast Phantom With Tumor Using Beamentioning
confidence: 98%
“…22,23 Many of the investigators did not authenticate their method experimentally using mimic of female breast. 24,25 The proposed monostatic method implicates the usage of a UWB antenna for microstrip patch antennas for RBMI. 16,[23][24][25] This concludes that the breast cancer detection using proposed antenna is efficient than the existing research in the field of biomedical applications.…”
Section: Delay Multiply and Summentioning
confidence: 99%